The Storing Matter technique applied to Alq3: influence of the collector material and the sputter‐deposition energy on fragmentation. (18th December 2012) - Becker, N.; Wirtz, T.; Migeon, H.‐N.
<x xml:space="preserve">Abstract</x> The Storing Matter technique is derived from secondary ion mass spectrometry (SIMS) and consists in decoupling the sputtering of the specimen from the analysis step. In a dedicated prototype instrument, the sample surface is bombarded by an ion beam, and the sputtered particles are deposited at sub‐monolayer level onto a collector. In a second step, this deposit is analyzed by SIMS (static or dynamic). In this work, we applied the Storing Matter technique to tris(8‐hydroxyquinolinato)aluminum (Alq3), a common component of organic light‐emitting diodes. Alq3 was sputter‐deposited onto Ag and Si collectors with different impact energies ranging from 3.75 keV to 10 keV. Positive mass spectra of these deposits and of an Alq3 reference sample were acquired under static SIMS conditions with 10‐keV impact energy. The intensity ratios of the characteristic Alq3 peaks are very similar for the Alq3 reference spectrum and the Storing Matter deposit with 10 keV, which indicates that most of the organic fragments deposited on the collector do not undergo a second fragmentation during the analysis step. This is however not the case for the same deposit on a Si collector. As the impact energy used for the sputter‐deposition step decreases, the peak distribution is shifted in favor of the smaller fragments, indicating a higher level of fragmentation. Copyright © 2012 John Wiley & Sons, Ltd.